2021
DOI: 10.17235/reed.2021.8007/2021
|View full text |Cite
|
Sign up to set email alerts
|

Mild ast elevation as an early sign of COVID-19 severity in a multicenter Madrid cohort

Abstract: Author contributions: C.F.C. performed data acquisition and analysis, contributed to site coordination, and was responsible for the first version of the manuscript. C.P. and E.L. contributed to data analysis and critical revision of the results and the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…In the present study, we similarly found that SARS-CoV-2 + rhinovirus coinfection, compared to SARS-CoV-2 mono-infection, was associated with lower laboratory biomarkers, specifically lower median ALT, AST, and CRP. These laboratory tests have been found to be raised in patients with more severe COVID-19 disease [33][34][35][36][37][38][39]. Further research is needed to investigate the discrepancy between 30-day mortality and laboratory biomarkers, but we hypothesize that respiratory symptoms may predominate early on in the disease course of patients with SARS-CoV-2 co-infections, which may necessitate hospital care before markers of systemic inflammation and organ involvement rise.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, we similarly found that SARS-CoV-2 + rhinovirus coinfection, compared to SARS-CoV-2 mono-infection, was associated with lower laboratory biomarkers, specifically lower median ALT, AST, and CRP. These laboratory tests have been found to be raised in patients with more severe COVID-19 disease [33][34][35][36][37][38][39]. Further research is needed to investigate the discrepancy between 30-day mortality and laboratory biomarkers, but we hypothesize that respiratory symptoms may predominate early on in the disease course of patients with SARS-CoV-2 co-infections, which may necessitate hospital care before markers of systemic inflammation and organ involvement rise.…”
Section: Discussionmentioning
confidence: 96%